PKC-mediated phosphorylation and activation of the MEK/ERK pathway as a mechanism of acquired trastuzumab resistance in HER2-positive breast cancer - Scerri, Jeanesse; Scerri, Christian; Schäfer-Ruoff, Felix; Fink, Simon; Templin, Markus; Grech, Godfrey (Frontiers in Endocrinology, 2022)
Protein expression, activation and stability are regulated through inter-connected signal transduction pathways resulting in specific cellular states. This study sought to differentiate between the complex mechanisms of intrinsic and acquired trastuzumab resistance, by quantifying changes in expression and activity of proteins (phospho-protein profile) in key signal transduction pathways, in breast cancer cellular models of trastuzumab resistance. To this effect, we utilized a multiplex, bead-based protein assay, DigiWest®, to measure around 100 proteins and protein modifications using specific antibodies. The main advantage of this methodology is the quantification of multiple analytes in one sample, utilising input volumes of a normal western blot. The intrinsically trastuzumab-resistant cell line JIMT-1 showed the largest number of concurrent resistance mechanisms, including PI3K/Akt and RAS/RAF/MEK/ERK activation, β catenin stabilization by inhibitory phosphorylation of GSK3β, cell cycle progression by Rb suppression, and CREB-mediated cell survival. MAPK (ERK) pathway activation was common to both intrinsic and acquired resistance cellular models. The overexpression of upstream RAS/RAF, however, was confined to JIMT 1; meanwhile, in a cellular model of acquired trastuzumab resistance generated in this study (T15), entry into the ERK pathway seemed to be mostly mediated by PKCα activation. This is a novel observation and merits further investigation that can lead to new therapeutic combinations in HER2-positive breast cancer with acquired therapeutic resistance.